2021
DOI: 10.1111/jomf.12752
|View full text |Cite
|
Sign up to set email alerts
|

Nonresident Fathers' and Grandparents' Early Years Support and Middle Childhood Socio‐Emotional Adjustment

Abstract: Objective This study investigates how different patterns of nonresident father support for children and mothers in the early years predict middle childhood adjustment, and whether grandparent support has compensating effects. Background Nonresident fathers' involvement in children's lives benefits socio‐emotional adjustment, but it is unclear whether support directed at children is compromised by interparental tensions, or whether other factors may compensate for weaker patterns of father support. Method Laten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 66 publications
0
1
0
Order By: Relevance
“…For example, using the latent class analysis, a recent study has identified four levels of nonresidential fathers' support: none, low, moderate, and high. In this study, the classes categorized by the level of father support were negatively associated with behavioral problems of children aged 4–10 years (Parkes et al, 2021). Another study using growth mixture modeling from children ages 3–9 found four distinct trajectories of coparenting quality among unmarried mothers and fathers: high–high, high–low, low–high, and low–low (Goldberg & Carlson, 2015).…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…For example, using the latent class analysis, a recent study has identified four levels of nonresidential fathers' support: none, low, moderate, and high. In this study, the classes categorized by the level of father support were negatively associated with behavioral problems of children aged 4–10 years (Parkes et al, 2021). Another study using growth mixture modeling from children ages 3–9 found four distinct trajectories of coparenting quality among unmarried mothers and fathers: high–high, high–low, low–high, and low–low (Goldberg & Carlson, 2015).…”
Section: Introductionmentioning
confidence: 80%
“…The other large proportion (77%) of parents who did not participate in the study might present additional profiles. Similarly, other caregivers such as grandparents (e.g., Parkes et al, 2021) and relatives (Epstein et al, 2015) also play important roles in raising children, but the data were unavailable regarding their coparenting. Second, we used the average scores of coparenting across 9 years, but the family is a dynamic system subject to changes (Watson, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned previously in the discussion section, a high number of Chilean adolescent fathers do not live with their child [ 89 ]. Additionally, the development of children born of adolescent mothers may be enhanced by the presence of grandparents when the father is absent [ 102 ], since Chilean adolescent mothers need support in childcare [ 13 , 15 , 16 , 103 ]. It has been shown that a large number of Chilean grandmothers share the responsibilities in the provision of care for children [ 104 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that extended family support for adolescent mothers can contribute to maternal satisfaction [30]. In fact, child development may be less affected if grandparents offer protection against the adverse effects of fatherlessness [31]. Furthermore, childcare support for adolescent mothers encourages them to be more affectionate with their babies [32].…”
Section: Chilean Adolescent Mothers' Sociodemographic Context and Chi...mentioning
confidence: 99%